2021
DOI: 10.2196/preprints.27384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual Mind-Body Programming for Patients With Cancer During the COVID-19 Pandemic: Qualitative Study (Preprint)

Abstract: BACKGROUND Patients with cancer are particularly vulnerable to stress and anxiety during the COVID-19 pandemic. Social distancing is critical for patients with cancer, yet this can also reduce access to psychosocial coping resources. OBJECTIVE This study aimed to identify how virtual mind-body programs impact patients’ psychosocial well-being during COVID-19. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Although we did not assess the participants' satisfaction through objective measurement, the parents who could tell the effect on their children through their facial expressions, actions, postures and voices at a close distance mentioned that the children grew brighter and happier and were satisfied after completing a regular physical activity. This is in line with the results of a previous qualitative study of the effects of a videoconferencing‐based programme, which comprised fitness, yoga, tai chi, dance therapy, music therapy and meditation, on patients with cancer (Emard et al, 2021). The programme strengthened the psychological coping of participants, provided motivation and promoted adherence to health behaviours (Emard et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although we did not assess the participants' satisfaction through objective measurement, the parents who could tell the effect on their children through their facial expressions, actions, postures and voices at a close distance mentioned that the children grew brighter and happier and were satisfied after completing a regular physical activity. This is in line with the results of a previous qualitative study of the effects of a videoconferencing‐based programme, which comprised fitness, yoga, tai chi, dance therapy, music therapy and meditation, on patients with cancer (Emard et al, 2021). The programme strengthened the psychological coping of participants, provided motivation and promoted adherence to health behaviours (Emard et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with the results of a previous qualitative study of the effects of a videoconferencing‐based programme, which comprised fitness, yoga, tai chi, dance therapy, music therapy and meditation, on patients with cancer (Emard et al, 2021). The programme strengthened the psychological coping of participants, provided motivation and promoted adherence to health behaviours (Emard et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…During COVID-19 restrictions, many yoga classes transitioned to telemedicine, yet there remain few published reports. [21][22][23][24] Among these, 2 studies transitioned from inperson to online intervention delivery during COVID-19 22,23 and a third study offered a variety of mind-body sessions to support psychological coping. 24 All these studies were conducted in group or dyad setups and found virtual yoga delivery acceptable and beneficial during COVID-19 social distancing restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Among these, 2 studies transitioned from inperson to online intervention delivery during COVID-19 22,23 and a third study offered a variety of mind-body sessions to support psychological coping. 24 All these studies were conducted in group or dyad setups and found virtual yoga delivery acceptable and beneficial during COVID-19 social distancing restrictions. There are no studies reporting oneon-one yoga via telehealth in cancer populations during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for virtually delivered interventions to manage IBS is increasing due to limited healthcare resources and higher cost-effectiveness (16,17). A yoga program delivered virtually is convenient, feasible, and effective in a COVID-19 setting in other diseases (e.g., cancer, heart disease, or chronic obstructive pulmonary disease) (18)(19)(20) and postpandemic where virtual care is accepted and expected. Effectiveness outcomes from these intervention nonrandomized studies included improved symptoms and functional performance, QOL, sleep quality, mental health, and reduced fatigue.…”
Section: Introductionmentioning
confidence: 99%